The COL5A1 gene, ultra-marathon running performance, and range of motion - Brown, J. C.; Miller, C. -J.; Posthumus, M.; Schwellnus, M. P.; Collins, M. (International Journal of Sports Physiology and Performance, 2011)
Purpose: Endurance running performance is a multifactorial phenotype that is strongly associated with running economy. Sit and reach range of motion (SR ROM) is negatively associated with running economy, suggesting that reduced SR ROM is advantageous for endurance running performance. The COL5A1 gene has been associated with both endurance running performance and SR ROM in separate cohorts. The aim of this study was to investigate whether COL5A1 is associated with ultra-marathon running performance and whether this relationship could be partly explained by prerace SR ROM. Methods: Seventy-two runners (52 male, 20 female) were recruited from the 56 km Two Oceans ultra-marathon and were assessed for prerace SR ROM. The cohort was genotyped for the COL5A1 BstUI restriction fragment length polymorphism, and race times were collected after the event. Results: Participants with a TT genotype (341 ± 41 min, N = 21) completed the 56 km Two Oceans ultra-marathon significantly (P = 0.014) faster than participants with TC and CC genotypes (365 ± 39 min, N = 50). The COL5A1 genotype and age accounted for 19% of performance variance. When the cohort was divided into performance and flexibility quadrants, the T allele was significantly (P = 0.044) over-represented within the fast and inflexible quadrant. Conclusion: The COL5A1 genotype was found to be significantly associated with performance in a 56 km ultra-endurance run. This study confirms previous findings and it furthers our understanding of the relationships among ROM, COL5A1, and endurance running performance. We continue to speculate that the COL5A1 gene alters muscle-tendon stiffness.